Anti-atherosclerotic Effect of Cilostazol in Apolipoprotein-E Knockout Mice - Takase, Hiromichi; Hashimoto, Ayako; Okutsu, Reiko; Hirose, Yoshimi; Ito, Hideki; Imaizumi, Takashi; Miyakoda, Goro; Mori, Toyoki (Arzneimittelforschung, 2007)
To investigate whether cilostazol (CAS 73963-72-1), a selective phosphodiesterase 3 inhibitor, reduces the progression of atherogenic diet-induced atherosclerosis, cilostazol was orally administered twice a day for 4 weeks to male apolipoprotein-E knockout (ApoE KO) mice. In serial sections of the aortic root, the atherosclerotic lesion ratios in the cilostazol-treated groups (32.5 ± 3.3 % for 100 mg/kg, 29.0 ± 2.9% for 300 mg/kg) were significantly and dose-dependently smaller than that of the control group (40.2 ± 3.7%). Cilostazol also significantly reduced the expression of vascular cell adhesion molecule-1 (VCAM-1) and monocyte/macrophage accumulation in the aortic root and increased high-density lipoprotein (HDL) cholesterol levels in plasma. These results suggest that cilostazol suppresses the progression of atherosclerosis in ApoE KO mice by inhibiting adhesion and infiltration of monocytes and reducing cholesterol accumulation in atherosclerotic lesion.
Keywords: Adhesion molecules; Anti-atherosclerosis agent; CAS 73963-72-1; Cilostazol, anti-atherosclerotic effect, ApoE knockout mice; HDL-cholesterol